Implementation of Strengthening Government Institutions Towards a Clear and Clean Bureaucratic Order in South Sulawesi Province - Ansar Amir; Darwis Nur Tinri; Nuddin Mahmuda (Syntax Corporation Indonesia, 2022)
A clear and clean government bureaucratic order is a priority in realizing structured, coordinated, organized and integrated institutions to improve relations between organizations, lower levels and target groups. This study aims to explain the implementation of institutional strengthening and the determinants of successful implementation towards a clear and clean bureaucratic order, as well as examine the determining factors of a successful implementation of government institutions. Types of phenomenological research qualitative approach. The research was conducted in the scope of government for two months by interviewing informants in depth scientifically, experience and historical traces in the field of government. The netting of data and information is obtained from primary and secondary data sources using triangulation techniques. Data analysis uses information reduction, presentation, verification and drawing conclusions based on the validity of the data. The results of the study found 1) institutional strength between organizations produces organizational structure, cooperation, interests and achievement of goals; 2) lower-level institutional strength produces coordination, counseling, monitoring and evaluation; and 3) the institutional strength of target groups results in advocacy, maintenance, simulation and participation